Scandinavian Journal of Pain : Official Journal of the Scandinavian Association for the Study of Pain (De Gruyter, 2010)
The Scandinavian Journal of Pain is the scientific journal of the Scandinavian Association for the Study of Pain. It serves as a comprehensive forum for original research on all aspects of pain and also publishes topical reviews to bring pain-researchers and pain-clinicians up-to-date on important issues.